2014
DOI: 10.1002/maco.201307458
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on anticorrosion performance of polyaniline‐mesoporous MCM‐41 composites in new water‐based epoxy coating

Abstract: Mesoporous MCM‐41(M(with template)) whose pore channels were filled with cationic surfactant n‐hexadecyltrimethyl‐ammonium bromide (CTAB) and a (hydrophobic) poly(propylene glycol) nucleus terminated by two primary hydroxyl groups (Pluronic F‐127, molecular weight = 11500) inside the pore channels and on the outer surface of the particle, MCM‐41 (M(without template)) whose mixture template inside the pore channels and on the outer surface of the particle were calcinated, were used as new fillers for waterborne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Meso-TiO 2 not only has nanoscale size, but also has the unique pore structure compared with normal nanoparticles which could improve the anti-aging properties and barrier properties of the coating. In our previous work, we proved that waterborne epoxy resin has better anticorrosion properties due to the addition of MCM-41 and we also proved that meso-TiO 2 can increase the barrier performance of the coatings more availably due to the larger pore size of meso-TiO 2 than MCM-41 [1,11]. However, due to high surface tension of water, the compatibility between waterborne epoxy matrix and filler is poor.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Meso-TiO 2 not only has nanoscale size, but also has the unique pore structure compared with normal nanoparticles which could improve the anti-aging properties and barrier properties of the coating. In our previous work, we proved that waterborne epoxy resin has better anticorrosion properties due to the addition of MCM-41 and we also proved that meso-TiO 2 can increase the barrier performance of the coatings more availably due to the larger pore size of meso-TiO 2 than MCM-41 [1,11]. However, due to high surface tension of water, the compatibility between waterborne epoxy matrix and filler is poor.…”
Section: Introductionmentioning
confidence: 69%
“…The BJH (aperture distribution test) analyses showed that meso-TiO2 exhibited an average poresize of about 5.8 nm calculated from the desorption branch of the nitrogen adsorption isotherm [1]. Table 2 shows that the pore volume of modified with dopamine decreased from 0.235 to 0.074 mL·g −1 compared with the pore volume of meso-TiO2.…”
Section: Nitrogen Adsorption-desorption Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Various reports have shown that the corrosion resistances of coatings can be improved with the addition of nanoparticles such as TiO2 [16], SiO2 [17], and ZnO [18]. In our previous work, we utilized mesoporous-TiO2 and MCM41 in corrosion-resistant coatings and showed that these nanoparticles enhanced the barrier properties of the coatings by reducing the transport paths for the corrosive electrolytes to pass through the coating system [19,20]. However, the synergistic corrosion protection of molecular sieve and graphene has not been reported in the field.…”
Section: Introductionmentioning
confidence: 99%